Eksplorasi Pembelajaran Berbasis Genre Dalam Penguatan Keterampilan Menulis Siswa - Anita Candra Dewi (FKIP UNSULTRA, 2025)
This literature review aims to explore the effectiveness of genre-based learning in strengthening students’ writing skills across educational levels. Grounded in systemic functional linguistics, this approach views language as a tool for constructing meaning within social contexts. Genre-based learning emphasizes understanding text structures, communicative purposes, and linguistic features of various genres such as narrative, descriptive, expository, and argumentative texts. The findings indicate that the genre-based approach consistently enhances students’ writing quality in terms of content, organization, grammar, cohesion, and coherence. The commonly applied model is the Teaching and Learning Cycle (TLC), consisting of four key stages: building knowledge of the field, modeling of text, joint construction of text, and independent construction of text. This approach also fosters metacognitive awareness, collaboration, and critical thinking in writing activities.